First record of Muellerius capillaris (Nematoda, Protostrongylidae) in northwestern Argentina - Suarez, Victor Humberto; Bertoni, Emiliano Agustín; Micheloud, Juan Francisco; Cafrune Wierna, María Mercedes; Viñabal, Alberto; Quiroga Roger, Juan Alfonso; Bassanetti, Alejandro Fabian (Springer, 2018)
Seven flocks of different composition of goat and/or sheep were evaluated for the presence of Muellerius capillaris (Mueller 1889) in sites of different climatic conditions and under different management practices in northwestern Argentina. The nematode was recovered and identified in four goat flocks and two mixed goat and sheep flocks. Three goat flocks and both mixed goat and sheep flocks were located in Lerma Valley (Salta), with the other goat flock located in Quebrada de Humahuaca (Jujuy). M. capillaris was not detected in the Puna of Jujuy (3500 m a.s.l.). First-stage larvae were recovered from fecal samples using the Baermann technique. Lungs from six goats revealed numerous small pulmonary nodules and areas of emphysema, as well as a small number of M. capillaris adults. This is the first report of M. capillaris in Argentina.